Case report: Total arch replacement with a frozen elephant trunk utilizing open hybrid in-situ fenestration technique for thoracic aortic arch aneurysm - Takei, Yusuke; Wu, I-Hui; Chan, Chih-Yang; Chi, Nai-Hsin (Frontiers in Surgery, 2023)
The frozen elephant trunk technique is a surgical procedure developed for concomitant repair of downstream descending thoracic aorta as a first stage operation for arch resections. Proximalization of the sutured anastomosis reduces technical difficulty of total arch replacement.to reduce the risk of bleeding and recurrent laryngeal nerve injury during the treatment of thoracic aortic aneurysms. In this procedure, an anastomosis is performed more proximally using a stent graf. tConnect the head and neck vessels are created using in-situ fenestration method. . However, the feasibility of the frozen elephant trunk procedure in cervical branch reconstruction, which is associated with vascular injury and bleeding, has not been established.This study presents the case of a 78-year-old woman with a large thoracic aortic arch aneurysm that was successfully treated with a modified frozen elephant trunk technique (open in situ fenestration). For this method, a hole was created in the neck branches (the left subclavian artery and left common carotid artery), and peripheral stent grafts were placed to simplify neck branch reconstruction. This minimized the risk of recurrent laryngeal nerve injury and bleeding and shortened the procedure time.The outcomes of this study showed a safe alternative total arch replacement procedure.